Potential interaction between autophagy and auxin during maize leaf senescence. (4th March 2021) - Feng, Xue; Liu, Lili; Li, Zhigang; Sun, Fang; Wu, Xiaoyuan; Hao, Dongyun; Hao, Huaiqing; Jing, Hai-Chun
Abstract : The timing of maize leaf senescence is potentially modulated by the interaction between autophagy and auxin, as revealed by the effects of the allelic combinations of ZmATG18b and ZmGH3.8 . Abstract: Leaf senescence is important for crop yield as delaying it can increase the average yield. In this study, population genetics and transcriptomic profiling were combined to dissect its genetic basis in maize. To do this, the progenies of an elite maize hybrid Jidan27 and its parental lines Si-287 (early senescence) and Si-144 (stay-green), as well as 173 maize inbred lines were used. We identified two novel loci and their candidate genes, Stg3 ( ZmATG18b ) and Stg7 ( ZmGH3.8 ), which are predicted to be members of autophagy and auxin pathways, respectively. Genomic variations in the promoter regions of these two genes were detected, and four allelic combinations existed in the examined maize inbred lines. The Stg3 Si-144 / Stg7 Si-144 allelic combination with lower ZmATG18b expression and higher ZmGH3.8 expression could distinctively delay leaf senescence, increase ear weight and the improved hybrid of NIL- Stg3Si-144 / Stg7Si-144 × Si-144 significantly reduced ear weight loss under drought stress, while opposite effects were observed in the Stg3 Si-287 / Stg7 Si-287 combination with a higher ZmATG18b expression and lower ZmGH3.8 expression. Thus, we identify a potential interaction between autophagy and auxin which could modulate the timing of maize leaf senescence.